The correlation between response time and waiting time on patients’ satisfaction at the emergency departement - Wasis Sapto Putro; Sodikin (Proceedings Series on Health & Medical Sciences, 2020)
Fast and accurate services are essential in the Emergency Departement (ED). Services in the emergency room will be hampered if it is are full of patients. If this is not managed well, the right services cannot be implemented. In turn, it will have a bad effect on patient satisfaction. To analyze the correlation between response time and waiting time with patient satisfaction during service at the Emergency Department of the Banyumas Regional General Hospital.This research is quantitative research. The sampling technique in this study used purposive sampling of 96 respondents. The statistical test used is the chi square test.Most respondents percieved the responding time in ER is fast; most of them also rated that the waiting time in ER is short. Most of them are also satisfied with ER services. The chi square test results in p value of <0.05 for each variable. It means there is a relationship between response time and waiting time with patient satisfaction during service at the Emergency Department of Banyumas Regional General Hospital.Response time and waiting time are related to patient satisfaction during service at the Emergency Department of Banyumas Regional General Hospital.